Data science for cyber-security - Heard, Nick; Adams, Niall; Rubin-Delanchy, Patrick; Turcotte, Melissa (Security science and technology, 2019)
Cyber-security is a matter of rapidly growing importance in industry and government. This book provides insight into a range of data science techniques for addressing these pressing concerns. The application of statistical and broader data science techniques provides an exciting growth area in the design of cyber defences. This volume presents contributed papers from an international conference of the same name held at Imperial College. Experts from the field have provided their latest discoveries and review state of the art technologies.